Seasonal Trends in Acoustic Detection of Marine Mammals in Baffin Bay and Melville Bay, Northwest Greenland + Supplementary Appendix 1 (See Article Tools) - Frouin-Mouy, Héloïse; Kowarski, Katie; Martin, Bruce; Bröker, Koen (ARCTIC, 2017)
The expansion of hydrocarbon exploration in northwest Greenland has made it increasingly important to understand the occurrence of marine mammals in the region. We describe the seasonal occurrence of marine mammals and the spatial distribution of their calls in Baffin Bay and Melville Bay. Four Autonomous Multichannel Acoustic Recorders (AMARs) were deployed during summer 2012 (late July to early October), five recorders during September 2013, and two recorders from late September 2013 to early September 2014. The call presence of several species was analyzed using automatic call detection and manual verification analysis methods. A novel approach to discern narwhal (Monodon monoceros) clicks from beluga (Delphinapterus leucas) clicks was implemented during the verification process. Narwhal calls were detected in spring and fall, showing a south-to-north migration pattern in spring and a north-to-south migration pattern in fall. Few beluga whales were detected during fall 2013 and spring 2014. Bearded seal (Erignathus barbatus) calls were detected mainly during spring (mating period). A small number of bowhead whale calls (Balaena mysticetus) were detected during fall 2013 and spring and summer 2014. For the first time at this latitude in Baffin Bay, long-finned pilot whales (Globicephala melas) and sperm whales (Physeter macrocephalus) were detected during summer and fall. Our results suggest that the presence of marine mammals in Baffin Bay and Melville Bay is governed mainly by the annual cycle of sea ice formation and decay. Le développement de l’exploration des hydrocarbures dans le nord-ouest du Groenland rend indispensable une meilleure compréhension de la présence des mammifères marins dans la région. La distribution saisonnière et spatiale des vocalisations de mammifères marins dans la baie de Baffin et la baie Melville sont décrites. Quatre AMAR (enregistreurs acoustiques autonomes multicanaux) ont été déployés durant l’été 2012 (de la fin de juillet au début d’octobre), cinq enregistreurs en ...